KONSEP EVALUASI PENDIDIKAN DALAM PERSPEKTIF ALQURAN - Syahril Syahril (State Institute of Islamic Studies (IAIN) Palu, 2007)
This article deals with the concept of education evaluation from the Qur’anic perspective. Evaluation is a popular term much used in education to know a student’s performance in education. In this context, in the Qur’an, we also find some terms that have similar meaning with evaluation. For example, al-inba’, al-hisab, al-bala, al-nadzar, al-wazn, al-fitnah al-taqdir . These terms are used by the Qur’an to evaluate God’s servants, either those who believe or disbelieve in God. To know further, how and in which context the Qur’an uses those terms, the usages of the terms are elaborated in this article.Kata Kunci: evaluasi pendidikan, Alquran, al-fitnah, al-hisab, al-wazn, al-taqdir